2016
DOI: 10.1158/1078-0432.ccr-15-2456
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Reprogramming Regulates Breast Cancer Progression

Abstract: Purpose: The goal of this study was to understand the role of altered mitochondrial function in breast cancer progression and determine the potential of the molecular alteration signature in developing exosome-based biomarkers.Experimental Design: This study was designed to characterize the critical components regulating mitochondrial function in breast tumorigenesis. Experiments were conducted to assess the potential of these molecules for exosome-based biomarker development.Results: We observed a remarkable … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 44 publications
0
61
0
Order By: Relevance
“…This was accompanied by decreased lung and liver metastases and primary tumor growth (49). SH3GL2 depletion reversed this phenotype (49). This indicates that the anti-tumor functions of Mfn2 are also mitochondrial-dependent.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…This was accompanied by decreased lung and liver metastases and primary tumor growth (49). SH3GL2 depletion reversed this phenotype (49). This indicates that the anti-tumor functions of Mfn2 are also mitochondrial-dependent.…”
Section: Discussionmentioning
confidence: 92%
“…Although the absence of the p21 Ras motif or the PKA phosphorylation site at Ser442 of Mfn2 has no effect on its mitochondrial membrane localization (3), altered mitochondrial function in breast cancer has been observed (49). In breast cancer cells, with the overexpression of Mfn2, the vesicular endocytosis-associated protein, SH3 domain-containing GRB2-like protein 2 (SH3GL2), was demonstrated to translocate to mitochondria, and induce the production of superoxide and the release of cytochrome C from the mitochondria to the cytoplasm (49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5a,b arrowheads). We observed an EMT phenotype (arrowheads) as determined by cell morphology3132 accompanied by an increased invasion (p = 0.0001) of both the cell lines following the exosomes treatment (Fig. 5a,b).…”
Section: Resultsmentioning
confidence: 80%
“…Recently, the pro-apoptotic and anti-proliferative effects of Mfn2 in different types of cancers have been studied, including liver, breast and urinary bladder cancers [22-24]. Mfn2 is frequently lost in breast cancer, which has influence on breast cancer progression by a new mitochondria reprogramming pathway [17], and the PI3K-AKT-mTOR pathway plays an important role in the activation-induced downregulation of Mfn2 and the subsequent proliferation of resting human T cells [25]. In our early study, we found that the PTD4-apoptin fusion protein could induce HeLa cell apoptosis and upgrade Mfn2 expression [26].…”
Section: Introductionmentioning
confidence: 99%